Pengaruh Kompetensi Kepribadian Guru Pendidikan Agama kristen dan Budi Pekerti Terhadap Tingkah Laku Siswa Kelas VII SMP Negeri 3 Lintongnihuta Tahun pembelajaran 2023/2024 - Monika Febiyola Br Pandia; Risden Anakampun; Simion D. Harianja (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
The aim of this research is to determine the influence of Christian Religious Education Teachers' Personality Competencies and Character on the Behavior of Class VII students at SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year. The research method used is a quantitative method with a descriptive and inferential approach. The population is all class VII students of SMP N 3 Lintongnihuta, North Tapanuli Regency for the 2023/2024 academic year, 164 of whom are Protestant Christians and a sample of 41 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 30 items, namely 15 items for variable 2023/2024, proven through the following data analysis: 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.518 > rtable(a=0.05,n=41) = 0.316. b) Testing a significant relationship obtained tcount= 3.782 > ttable(a=0.05, dk=n-2=39)= 2.021. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂=